Overwhelming Pulmonary Infection after a Tobogganing Accident - Ravinder Singh; Brian E Louie; William F Bennett; Christopher Allen; Tom Kelly; Christine H Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 17-year-old male patient presented to St Joseph's Healthcare (Hamilton, Ontario) with a radiologically opacified left hemithorax. Three days earlier, the patient had injured his left lower chest while tobogganing on his farm. He developed dyspnea and felt unwell, but only sought medical attention from his family doctor a few days after the injury, when fever and pleuritic chest pain ensued. He was treated with a nonsteroidal anti-inflammatory agent, but his chest radiograph revealed an opacified hemithorax, for which he was referred to the hospital. In the emergency department, the patient looked ill and was in distress. His heart rate was 125 beats/min, and he had a blood pressure of 103/61 mmHg, a respiratory rate of 20 breaths/min, a temperature of 38.5°C and an oxygen saturation of 94% on ambient air. Laboratory results showed a white blood cell count of 40×109/L with a left shift. Chest radiography showed a left pleural effusion. A #28 Fr chest tube was inserted into the left hemithorax, and foul-smelling serosanguineous fluid was drained. There was a transient improvement of tachypnea and hypoxemia despite minimal radiographic change. He was admitted and subsequently started on intravenous levofloxacin. Overnight, he deteriorated and required an increase in supplemental oxygen. A computed tomography (CT) scan of his chest revealed multiple loculated fluid collections and bilateral pulmonary parenchymal infiltrates consistent with a pneumonia and empyema.